Chromosomal macrodomains and associated proteins: implications for DNA organization and replication in gram negative bacteria. - Remus T Dame; Olga J Kalmykowa; David C Grainger (PLoS Genetics, 2011)
The Escherichia coli chromosome is organized into four macrodomains, the function and organisation of which are poorly understood. In this review we focus on the MatP, SeqA, and SlmA proteins that have recently been identified as the first examples of factors with macrodomain-specific DNA-binding properties. In particular, we review the evidence that these factors contribute towards the control of chromosome replication and segregation by specifically targeting subregions of the genome and contributing towards their unique properties. Genome sequence analysis of multiple related bacteria, including pathogenic species, reveals that macrodomain-specific distribution of SeqA, SlmA, and MatP is conserved, suggesting common principles of chromosome organisation in these organisms. This discovery of proteins with macrodomain-specific binding properties hints that there are other proteins with similar specificity yet to be unveiled. We discuss the roles of the proteins identified to date as well as strategies that may be employed to discover new factors.